Characteristics associated with attendance of follow-up at a post-rape care centre in Cape Town, South Africa - Ncube, Nozwelo Ntombizami (Department of Psychiatry and Mental Health, 2017)
BACKGROUND: Rape is associated with a range of negative health and mental health consequences. Despite the establishment of post-rape care centres in South Africa, challenges of retaining rape survivors in care continue to be faced across the country. Very little evidence on the characteristics associated with rape survivors who return for follow-up and those lost to care at post-rape care centres has been documented in South Africa. This study sought to identify the demographic factors, rape incident characteristics and social support factors that are associated with attendance of follow-up appointments at a post-rape care centre in Cape Town, South Africa. METHOD: A retrospective case file analysis was conducted on 254 files of rape survivors who presented and were given follow-up appointments at a post-rape care centre in Cape Town, South Africa from September 2010 to August 2011. Data were extracted using a data collection form which was developed using counselling and medical records in the survivors' files and analysed using SPSS version 21. Descriptive statistics were generated on the survivors' demographic information, rape incident information, medical information, and support systems. Chi-squared test and Fisher's exact test were used to test for differences between survivors who completed all their follow-up appointments, those who attended but did not complete follow-up appointments and those lost to care. RESULTS: Of the total sample 64.6% (164) attended their one week follow-up appointment. From those who attended their one week follow-up appointment, 47% (77) came for their six weeks appointment and approximately half of those who attended their six weeks appointments (51%, n=39) attended their three month appointments. Survivors of rape were significantly more likely to attend follow-up appointments if they were female, incurred injuries during the time of the rape, or received family support post-rape. CONCLUSIONS: Female gender, injury during rape and family support were associated with attendance of follow up care in this sample of rape survivors. Recommendations for future research and for enhancing attendance rates at rape treatment centres are considered.